International Law and the Concept of Peace in the International System - Osayi, Francis Osadebamwen (Kashere Journal of Politics and International Relations, 2023)
This study aspires to capture the evolution, operationalization as well as an appraisal of international law in the promotion of security and peace in the global arena. In furtherance of the study, the secondary source for data gathering was deployed to get the necessary information. There is no one who does not need the support and assistance of other person, which is the fact that no state is autarchy. The absence of absolute economic independence or self-reliance therefore compels the states to relate with one another in their abysmal drive towards economic, social, cultural and political satisfaction for their citizens. There are set of rules to guide the relationship among the states became expedient, in order to avoid or at the least, limit anarchy and chaos-a situation violent conflict hence, international law. It recommended that all issues of international law should be justiciable.